The Empowerment of Village Communities in Improving Family Welfare through Rattan Woven Training in Bag and Rattan Making - Susan Daniel; Wiwin Wiwin (Budapest International Research and Critics University, 2022)
The results of research that have been carried out can be conveyed that 1.empowerment of village communities in an effort to improve family welfare through rattan weaving training in buntoi village,Kahayan sub-district downstream,knife home district namely by: involving various agencies related to community empowerment and family welfare, providing outreach to prospective students directing and fostering students. 2. Supporting factors as follows: enthusiastic students in participating in activities, support from the government in the village of buntoi and the instructors' commitment to fostering students. Inhibiting factors, namely: funds, time and transportation.